AKUNTABILITAS PENGELOLAAN KEUANGAN DI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN BANGGAI KEPULAUAN PROVINSI SULAWESI TENGAH - SALDRAK, PUPUT; OGOTAN, MARTHA; LONDA, VERY (Sam Ratulangi University, 2018)
The accountability issues of financial management based on the overall activities including planning,implementation, administration, reporting, accountability and supervision are important aspects of localfinancial management so that this study aims to know the accountability of financial management inBanggai Island District Youth and Sports Education Department. This research uses qualitative descriptiveresearch method through data collection technique that is observation, interview and documentation. Withdata analysis techniques namely reduction, data presentation and conclusion. The findings of this studyindicate that budget users do not have integrity over their delegated positions, lack of strict supervision, lackof support facilities, and lack of administrative capability so that the tasks in the service are still slow.Various programs that are needed in part have been met to support the continuity of the existing education.With accountability of financial management has been submitted and evaluated by the authorities such asInspectorate, KPK, Attorney, BPK and implementations is in accordance with the required Department ofEducation Youth and Sports Banggai Islands in performing duties and functions. To improve theaccountability of financial management to realize accountable financial management while maintainingaccountability, participatory, responsive, and transparent principles as budget users should pay moreattention to and understand the tasks and functions of the delegated positions in accordance with the rulesand applicable laws. Conduct training, keep using and maintaining the Buttom-Up Planing model infinancial management planning, and conduct stricter supervision.Keywords: Accountability, Management, Finance